2022
DOI: 10.3389/fimmu.2022.902515
|View full text |Cite
|
Sign up to set email alerts
|

A Single Vaccination of Chimeric Bivalent Virus-Like Particle Vaccine Confers Protection Against H9N2 and H3N2 Avian Influenza in Commercial Broilers and Allows a Strategy of Differentiating Infected from Vaccinated Animals

Abstract: H9N2 and H3N2 are the two most important subtypes of low pathogenic avian influenza viruses (LPAIV) because of their ongoing threat to the global poultry industry and public health. Although commercially available inactivated H9N2 vaccines are widely used in the affected countries, endemic H9N2 avian influenza remains uncontrolled. In addition, there is no available avian H3N2 vaccine. Influenza virus-like particles (VLPs) are one of the most promising vaccine alternatives to traditional egg-based vaccines. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The efficacy and adaptability of subunit vaccines are underscored by their successful application in diverse pathogens, including influenza (Vogel and Manicassamy, 2020), SARS-CoV-2 Heidary et al, 2022), and RSV (Papi et al, 2023). Utilizing various platforms, such as recombinant protein vaccines (Liu et al, 2021;Chavda et al, 2024), virus-like particles (VLPs) (Sun et al, 2022), and nanoparticles (Pilkington et al, 2021), these vaccines have demonstrated considerable promise, with (Cao et al, 2022) M2e: The Matrix 2 ectodomain of influenza virus; NTD: The N-Terminal domain of the SARS-CoV-2 spike protein; HA1 trimer: trimerized hemagglutinin 1 of influenza virus; RBD trimer: trimerized receptor binding site of SARS-CoV-2 spike protein; IAV: influenza A virus.…”
Section: Combined Subunit Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy and adaptability of subunit vaccines are underscored by their successful application in diverse pathogens, including influenza (Vogel and Manicassamy, 2020), SARS-CoV-2 Heidary et al, 2022), and RSV (Papi et al, 2023). Utilizing various platforms, such as recombinant protein vaccines (Liu et al, 2021;Chavda et al, 2024), virus-like particles (VLPs) (Sun et al, 2022), and nanoparticles (Pilkington et al, 2021), these vaccines have demonstrated considerable promise, with (Cao et al, 2022) M2e: The Matrix 2 ectodomain of influenza virus; NTD: The N-Terminal domain of the SARS-CoV-2 spike protein; HA1 trimer: trimerized hemagglutinin 1 of influenza virus; RBD trimer: trimerized receptor binding site of SARS-CoV-2 spike protein; IAV: influenza A virus.…”
Section: Combined Subunit Vaccinesmentioning
confidence: 99%
“…The efficacy and adaptability of subunit vaccines are underscored by their successful application in diverse pathogens, including influenza ( Vogel and Manicassamy, 2020 ), SARS-CoV-2 ( Dong Y. et al., 2020 ; Heidary et al., 2022 ), and RSV ( Papi et al., 2023 ). Utilizing various platforms, such as recombinant protein vaccines ( Liu et al., 2021 ; Chavda et al., 2024 ), virus-like particles (VLPs) ( Sun et al., 2022 ), and nanoparticles ( Pilkington et al., 2021 ), these vaccines have demonstrated considerable promise, with several vaccines receiving approval for human use or currently undergoing clinical trials. Moreover, subunit vaccines serve as a highly adaptable platform for the development of combined vaccines, capable of targeting multiple strains of viruses like human papillomavirus (HPV) and influenza ( Liu et al., 2021 ; Williamson, 2023 ).…”
Section: Combined Subunit Vaccinesmentioning
confidence: 99%
“…A previous study reported the occurrence of apoptosis in the liver during virus infection in 7-day ducklings, providing partial insight into the mechanism of liver injury ( Cao et al, 2020 ). It is crucial to elucidate the underlying pathogenic mechanism to mitigate economic losses associated with viral infectious diseases ( Chen et al, 2022 ; Sun et al, 2022 ; Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to inactivated vaccines, current new research directions include virus-like particles [ 27 ], recombinant vector vaccines [ 28 ], live attenuated vaccines [ 29 ], nucleic acid vaccines [ 30 ], and subunit vaccines [ 31 ]. The development of different types of vaccines provides new options for the control of H9N2 AIV.…”
Section: Introductionmentioning
confidence: 99%